2015
DOI: 10.6002/ect.2014.0174
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: The logistics of deceased-donor renal transplants are largely affected by cold ischemia time. However, to attain successful outcomes, other issues must be considered. Extending cold ischemia time to accommodate these issues would be valuable. We investigated the role of hypothermic machine perfusion to extend cold ischaemia time. Materials and Methods: Deceased-donor kidneys were allocated to a storage method, depending on predicted time to operation. Kidneys to be transplanted from 8:00 AM to 8:00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 36 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…There were 2025 and 3229 patients receiving grafts treated with NRP and ISP, respectively. The NRP and ISP cohorts had similar mean donor age (48.1 Forest plot for post-transplant serum creatinine (mg/dL) between MP and SCS [9,15,17,24,27,28,31,[40][41][42][43][44][45]48,49,51,57].…”
Section: Normothermic Regional Perfusion (Nrp) Vs In Situ Cold Preser...mentioning
confidence: 99%
See 3 more Smart Citations
“…There were 2025 and 3229 patients receiving grafts treated with NRP and ISP, respectively. The NRP and ISP cohorts had similar mean donor age (48.1 Forest plot for post-transplant serum creatinine (mg/dL) between MP and SCS [9,15,17,24,27,28,31,[40][41][42][43][44][45]48,49,51,57].…”
Section: Normothermic Regional Perfusion (Nrp) Vs In Situ Cold Preser...mentioning
confidence: 99%
“…There were 22 (53.7%) studies that involved kidney pairs [17,[20][21][22]24,28,[30][31][32][33][34]36,41,[44][45][46][47][48]52,57]. Studies were conducted across the world; 25 (61.0%) were single-center efforts [9,17,22,[24][25][26][27][28][29][30]35,[38][39][40][41][42][43]45,46,48,49,51,54,55,57], while 16 (39.0%) involved multiple centers [15,20,21,23,[31]…”
Section: Machine Perfusion (Mp) Vs Static Cold Storage (Scs)mentioning
confidence: 99%
See 2 more Smart Citations
“…A Cochrane database review showed that open donor nephrectomy is associated with a higher risk of DGF than laparoscopic donor nephrectomy (relative risk of 1.09, 95% CI, 0.52-2.30). 61 Interestingly, results of kidney transplant between unrelated individuals in Western countries indicate that immunologic factors such as HLA matching, ABO incompatibility, 62 and longer cold ischemia time using advanced technology such as hypothermic machine perfusion 63 have minimal effect on DGF. Therefore, further studies are certainly warranted to investigate the effect of these factors on DGF from a Middle Eastern perspective to ensure high success rate in terms of graft function.…”
Section: Other Risk Factorsmentioning
confidence: 99%